An Efficient CAC scheme for IP traffic over wireless ATM networks - 299978 Husna Zainol Abidin; Norsheila Fisal; M. S. Ansari; Asia Pacific Conference on Communications (9th : 2003 : Pulau Pinang) (Skudai : Universiti Teknologi Malaysia, 2003)
13